Kambuik Kuantan Singingi culture for realistic mathematics education approach - Aulia Isroi; Sri Rezeki; Suripah Suripah (Universitas negeri Yogyakarta, 2022)
The mathematics learning tools used by teachers today are often less attractive and monotonous. Teachers are rarely objects in their culture. The environment around students can be utilized for the learning process. Many have argued that culture-based learning tools can be used in learning. This study aimed to validate mathematics learning instruments involving Kambuik Kuantan Singingi culture. The learning is intended to bed implemented based on the Realistic Mathematics Education (RME) approach in junior high school. The instrument was developed using the Plomp model. The validation data were collected using a set of questions. For the lesson plan, there were six aspects measured, namely the content, presentation, learning activities, learning resources, and assessment instruments, while for the worksheets, five aspects were included: content, didactic, construction, technical presentation, and time allocation. Three experts in the area were invited as validators. The results suggested that the learning instruments (lesson plans and worksheets) were valid to be implemented at school. It can be concluded that the Kambuik Kuantan Singingi culture can be used as a resource of learning in the RME framework.